Islamic Institution of Education in Bangladesh: A Study on Alia Madrasah - Momen, Abdul; Islam, Mohammad Khairul (Universitas Islam Negeri Mataram, 2025)
The paper examines the Alia Madrasah education system in Bangladesh, including its historical context, pedagogical framework, and role in delivering formal education as an institution. Alia Madrasahs are crucial in providing a combination of religious and modern education. However, these institutions encounter various obstacles, such as needing more competent professors, and a deficiency in implementing academic changes. The main goals of this study are to examine the potential of this educational system and emphasize the historical origins and establishment of Alia Madrasahs. This study utilizes a qualitative methodology, which includes analysing texts, doing a literature review, and observing insights. The study demonstrates that Alia Madrasahs have a pivotal function in delivering formal education to Muslim students in Bangladesh. The results of this study emphasize the significance of tackling the difficulties encountered by Alia Madrasahs, including the scarcity of competent educators and the necessity for academic improvements. By improving the educational standards in these institutions, Alia Madrasahs can effectively equip students with the necessary skills and knowledge for pursuing higher education and entering the job market. This will guarantee their competitiveness and success in today's educational environment.